Computational tools for the study of the genomes of filamentous fungi - L. Ellis; P. Ramos; J. Kirk; C. Floyd; J. Bender; Greg May; Tom Adams (Fungal Genetics Reports, 1994)
During the past year, we have developed and deployed several new computational tools to provide new means of access to information used for research in the biology of filamentous fungi. These new tools complement and extend other resources available for access to both molecular and biological data.